2015
DOI: 10.1080/02791072.2014.991858
|View full text |Cite
|
Sign up to set email alerts
|

Stigma among California’s Medical Marijuana Patients

Abstract: The enactment of California's Proposition 215 stipulates that patients may use marijuana for medical reasons, provided that it is recommended by a physician. Yet, medical marijuana patients risk being stigmatized for this practice. This paper examines the way in which medical marijuana patients perceive and process stigma, and how it affects their interactions and experiences with others. Eighteen semi-structured interviews of medical marijuana patients were carried out using a semi-structured interview guide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
107
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 41 publications
7
107
3
Order By: Relevance
“…In most studies, MMU was assessed based on self-reports and relied on a small subset of patients, which might lead to less reliable prevalence estimates. Especially, the accuracy of self-reported responses are subject to bias due to the stigma associated with MMU (Satterlund et al, 2015). In some studies, there was a lack of information on patient’s medical conditions, which might lead to inaccurate proportions of people using MM for pain.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, MMU was assessed based on self-reports and relied on a small subset of patients, which might lead to less reliable prevalence estimates. Especially, the accuracy of self-reported responses are subject to bias due to the stigma associated with MMU (Satterlund et al, 2015). In some studies, there was a lack of information on patient’s medical conditions, which might lead to inaccurate proportions of people using MM for pain.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived bias against MC and being viewed as a “pothead” or “stoner” has also been identified in studies of individuals in California. 25 Potential stigma may contribute to patients obtaining their certification for MC from healthcare providers with whom they do not have a long-term relationship. Effective healthcare delivery depends upon effective communication between patients and providers.…”
Section: Discussionmentioning
confidence: 99%
“…5 Similarly, interviews of MC patients in California revealed that the negative connotations associated with marijuana caused them to delay raising this topic with healthcare providers. 25 The objective of this report was to expand upon this foundation and examine both the strengths and limitations of MC in the northeastern United States.…”
Section: Introductionmentioning
confidence: 99%
“…§ 329-122, 2016). In addition, despite an overall increase in acceptance of cannabis, qualitative studies indicate that patients still report perception of stigma associated with its use (Bottorff et al, 2013; Gates, Copeland, Swift, & Martin, 2012; Satterlund, Lee, & Moore, 2015). Adolescent female recreational users also expressed concern about the lingering odor of cannabis following smoking (Friese, Slater, Annechino, & Battle, 2016).…”
Section: Promises Of Ediblesmentioning
confidence: 99%